Pengaruh Permainan Tradisional Congklak Bilangan Terhadap Pemahaman Matematis Siswa Materi KPK dan FPB Kelas V - Berlian Indriani; Fitri Apriani; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2026)
Students' inability to understand the concepts of Least Common Multiple (LCM) and Greatest Common Factor (GCF) is what spurred this study. It is still difficult for many students to understand factors, multiples, and derived word problems based on these two ideas. This challenge results from a dearth of interesting and distinctive instructional materials. This study aims to investigate the effects of the traditional number game congklak on the mathematical comprehension of fifth-grade pupils at SD Negeri 17 Sungaiselan. A True Experimental Design (TEST) Pretest-Posttest Only Control Design is the quantitative method used in this investigation. Twenty students from the experimental class and twenty from the control class participated in the study. Tests were used to gather data, which was subsequently examined. Using the independent sample t-test, homogeneity test, and Shapiro-Wilk test for normality, it was determined that the data were homogeneous and regularly distributed (p > 0.05). Because the t-test results showed a significant value of 0.007 < 0.05, the alternative hypothesis was accepted. Thus, pupils' mathematical understanding of the components of KPK and GCF is significantly improved by playing the traditional Congklak number game.